2015
DOI: 10.1016/j.jep.2015.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Developing an activity and absorption-based quality control platform for Chinese traditional medicine: Application to Zeng-Sheng-Ping(Antitumor B)

Abstract: Ethnopharmacological relevance Zeng-Sheng-Ping (ZSP) is a marketed Chinese traditional medicine used for cancer prevention. Aim of the study Currently, for the quality control of Chinese traditional medicines, marker compounds are not selected based on bioactivities and pharmaceutical behaviors in most of the cases. Therefore, even if the “quality” of the medicine is controlled, the pharmacological effect could still be inconsistent. The aim of this study is to establish an activity and absorption-based plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Zhou et al also showed that it was able to inhibit the growth of human ovarian A2780 and lung H23 cancer cells in vitro. The compound also has anti-proliferative activity in oral carcinoma SCC2095 cells [62]. A combination of trifolirhizin together with maackiain (a constituent of Trifolium pratense ) has been shown to induce apoptosis in human leukemia HL-60cells.…”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…Zhou et al also showed that it was able to inhibit the growth of human ovarian A2780 and lung H23 cancer cells in vitro. The compound also has anti-proliferative activity in oral carcinoma SCC2095 cells [62]. A combination of trifolirhizin together with maackiain (a constituent of Trifolium pratense ) has been shown to induce apoptosis in human leukemia HL-60cells.…”
Section: Traditional Chinese Medicines (Tcms) As Anti-cancer Agentsmentioning
confidence: 99%
“…Numerous epidemiological studies have indicated that vegetarian diets based on fruit and vegetable consumption are beneficial for human health [ 9 , 10 , 11 ], but the involved food components and the underlying mechanisms still remain unclear. Chinese traditional medicine has had a long history of applying crude plant extracts to treat diseases and disorders exemplified by acute and chronic inflammation [ 12 , 13 , 14 ]. Recent investigations have demonstrated that the polyphenols from plant sources, in particular flavonoids, exhibit anti-inflammatory activity both in vitro and in vivo [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the effective ingredients in most TCM are still unknown . It was reported that among the 1203 herbs included in the Chinese Pharmacopoeia (2010 version), only 529 could be regulated by reference compounds . Currently, there are about 500 herbal reference materials are available, but some unstable reference compounds are difficult to be obtained .…”
Section: Current Limitationsmentioning
confidence: 99%